Electroacupuncture Improves Cerebral Vasospasm and Functional Outcome of Patients With Aneurysmal Subarachnoid Hemorrhage - Sun, Jie; Liu, Yuchun; Zhang, Junjun; Chen, Xiaosheng; Lin, Zhiqing; Nie, Sheng; Shi, Manhua; Gao, Xiang; Huang, Yi (Frontiers in Neuroscience, 2018)
Cerebral vasospasm is the major cause of a poor outcome after aneurysmal subarachnoid hemorrhage (aSAH), and effective treatments for vasospasm are limited. The purpose of this study was to research the impact of electroacupuncture (EA) on cerebral vasospasm and the outcomes of patients with aSAH. A total of 60 age- and sex-matched aSAH patients were collected from Ningbo First Hospital between December 2015 and June 2017. All patients were given a basic treatment of nimodipine and randomized into two groups. The study group was treated with EA therapy on the Baihui (GV20) acupoint, and the control group was given mock transcutaneous electrical nerve stimulation. Cerebral vasospasm was measured by computed tomographic perfusion (CTP) and transcranial doppler (TCD). The mean flow velocity (MFV) in the middle cerebral artery (MCA), cerebral blood flow (CBF), cerebral blood volume (CBV) and mean transit time (MTT) of the patients were analyzed. The CBV and MTT exhibited significant differences between the study and control groups on the 1st (p = 0.026 and p = 0.001), 7th (p = 0.020 and p < 0.001) and 14th (p = 0.001 and p < 0.001) day after surgery, whereas CBF exhibited statistical significance only on the 14th day after surgery (p = 0.002). The MFV in MCA were significantly reduced after EA treatment in all patients (all p < 0.001). Additionally, the MFV in the MCA in patients treated with EA were considerably reduced compared with those of the control group (3rd day p = 0.046; 5th day, p = 0.010; 7th day, p < 0.001). Moreover, better outcomes were noted in the EA-treated group for the 1st month (p < 0.001) and 3rd month (p = 0.001) after surgery than in the control group. In conclusions, EA represents a potential method to treat cerebral vasospasm after aSAH and can improve the outcomes of patients with aSAH.